ASD transition to mainstream secondary: a positive experience?. Issue 4 (1st October 2016) - Neal, Sinead; Frederickson, Norah
Abstract: The transition to secondary school is considered difficult for children with autistic spectrum disorder (ASD), yet there has been little strength-based investigation of positive experiences of this population and the types of support they value most in managing anxiety about transition. The current article presents a qualitative exploration of the perspectives of six children with ASD who had recently transitioned successfully into mainstream secondary schools. Thematic analysis of semi-structured interview transcripts indicated that the children valued many changes associated with moving to secondary school (for example, greater routine, more varied lessons). In terms of intervention approaches, children favoured those that were positive in focus (for example, support from family, discussions about positive aspects of secondary school) and provided practical advice (for example, written information about secondary school, secondary school visits, opportunities to meet secondary school staff). Despite these commonalities, experiences varied and it was evident that children benefitted from individualised support tailored to their specific needs. Findings have implications concerning the support offered to children with ASD across secondary school transition and highlight the need to incorporate the child's voice into intervention plans.